Development of hybrid steel-commingled composites CF/PEEK/BwM by filament winding and thermoforming - Di Benedetto, Ricardo Mello [UNESP]; Janotti, Anderson; Gomes, Guilherme Ferreira; Ancelotti Junior, Antonio Carlos; Botelho, Edson Cocchieri [UNESP] (Elsevier, 2022)
A hybrid material made of carbon fiber, poly(ether-ether-ketone) and metallic braided wire mesh was designed to improve the crashworthiness of thermoplastic composite structures. The filament winding process was adapted to enable the winding of carbon fiber/poly(ether-ether-ketone) commingled tow with five different patterns of braided wire mesh, which were later consolidated by thermoforming. Samples of the hybrid steel-commingled composites were subjected to interlaminar shear strength tests, dynamic mechanical and thermomechanical analysis. Thermal analysis determined the glass transition, secondary temperature transitions, melting point, and the thermal expansion coefficient of CF/PEEK hybrid composites. The shear and thermal properties were investigated using statistical techniques of analysis of variance and design of experiments, highlighting the effects of the braided wire mesh parameters, i.e., mesh physical dimensions, on the material behavior. The incorporation of wire mesh showed no significant difference in the thermal properties of the hybrid composites and the applicability of these materials has no restrictive effect on temperature variations. An improvement of 22.7% in interlaminar shear strength was obtained for the hybrid metal-composite compared to the material without the braided wire mesh. Finally, a multiple regression model was developed to predict the interlaminar shear strength of hybrid steel-commingled composites as a function of the mesh parameters.
Keywords: Dynamic mechanical analysis; Interlaminar shear properties; Metal-composite structure; Structural composites; Thermomechanical analysis